Outcomes of the Southampton Wound Grading System in Punch Biopsy Wounds - Adhikari, Harihar; Pathak Thapa, Deeptara; Kumar Jha, Anil; Shrestha, Shristi; Joshi, Smita; Amatya, Bibush; Bhandari, Sajana (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Introduction: Skin biopsy punch is a common instrument used by dermatologists in day-to-day practice. The use of this device is associated with minimal complications. However, we cannot deny the possibility of adverse effects. We aimed to grade and track therapeutic skin punch biopsy wounds over 3 months using the Southampton Wound Grading System (SWGS). Materials and Methods: Selected patients in whom skin punch biopsy could be used therapeutically were enrolled. The procedures were performed under local anesthesia with suturing whenever needed. Immediate complications were noted, with follow-ups after 1 week, 1 month, and 3 months. The complications were noted, and the wounds were graded. Results: A total of 56 lesions from 45 patients underwent five procedures (punch excision, narrow hole extrusion technique, pinch-punch excision, enucleation of corn, and punch grafting). The most common immediate complication was a dog-ear defect; surgical wound dehiscence predominated at one week and one month, while post-inflammatory hyperpigmentation and hypertrophic scars were most common at three months. SWGS grades after one week were IC (67.86%), 0 (17.86%), IA (12.50%), and IIC (1.78%); after one month, 0 (64.29%) and IC (35.71%); after three months, 0 (76.79%) and IC (23.21%). Inferential analysis showed that larger punch sizes were associated with higher complication rates (p=0.049), and sutured wounds had more complications than non-sutured wounds (p=0.0028). Conclusion: There were predominantly minor complications like dog-ear defect and mild erythema, with no postoperative infections. Larger punch sizes and suturing were associated with more complications, underscoring careful punch selection and closure technique.